ANALISIS YURIDIS PUTUSAN NOMOR : 48/PDT.G/2011/PN.PRA TENTANG GADAI TANAH PERTANIAN - Lalu Muh. Rizaldi Bambang Septianto; Arief Rahman (Private Law, 2021)
This study describes the practice of mortgaging farmland according to the Law No 56 of 1960 of Farmland Area Setting, as well as figures out considerations taken by panel of judges in deciding Decree No 48/Pdt.G/2011/PN.Pra of Mortgaging Farmland. This study is a normative one, with statute, conceptual, and case approach. Results of this study show that arguments of plaintiff are taken as considerations in deciding the decree, as they comply with the Law No 56 of 1960 of Farmland Area Setting.